Layer-by-layer (chitosan/polystyrene sulfonate) membrane-based fabry-perot interferometric fiber optic sensor - Ang, Xiu Min (2011)
With the emergence of nanotechnology in the recent decade, application of nano-scaled deposition techniques in the fabrication of nanosensors, specifically fiber-optic nanosensors, has been fast rising, bringing with it various biological/biomedical-related applications. Principally, one such deposition technique of focus is the electrostatic molecular self assembly (ESA), also known as layer-by-layer (LBL) assembly. A label-free, LBL, fiber-optic interferometry biosensor for real-time affinity-based protein sensing applications has been proposed.